Correlation of Structural Changes and Hydrogen Diffusion in Polycrystalline WO3 Thin Films by Combining In Situ Transmission Measurements and Raman Spectroscopyin - Friedrich, Markus S.; Hecker, Tim K.; Strack, Alexander G.; Tuchecker, Paul; Klar, Peter J.; Justus Liebig University Giessen (My University, 2024)
Diffusion in polycrystalline tungsten trioxide (WO3) thin films is studied in a lateral geometry to better understand the impact of hydrogen-induced structural phase transitions on the diffusion. WO3 thin films are coated with polymethylmethacrylate layer (PMMA). The latter is microstructured in such a way that a narrow stripe-like gap occurs in the PMMA layer exposing the surface of the WO3 thin film. This stripe serves as the contact to the electrolyte in the intercalation experiment with hydrogen. After intercalation, the lateral diffusion of hydrogen inside WO3 below the PMMA layer can be observed, increasing the analyzable path and time scale by several orders of magnitude compared to the film thickness, thus, significantly improving spatial and temporal resolution of in situ transmission and Raman measurements. Spatially resolved transmission measurements in the wavelength range of 633±55 nm show that the diffusion process is dependent on hydrogen concentration and exhibits two regimes describable by different diffusion coefficients. Time-resolved Raman spectroscopic measurements at different distances from the electrolyte contact area show that the switching between the two diffusion coefficients occurs at the phase transition from the orthorhombic to the tetragonal phase. The results are further supported by a simulation. The measurement approach is universally applicable for electrochromic films or multilayers.
Keywords: ddc:530